On the way to information society five years of European ACTS research on intelligence in services and networks - Magedanz, Thomas (IOS Ohmsha, 2000)
This text addresses the issues in particular order and provides the results of IS&N projects addressing those issues in a synthesized manner, so that the reader can gain insights into the European projects contribution towards the telecommunications software industry.